Niacin requirement of broilers fed on a diet based on maize-palm kernel meal - R. A., Oloyo (Universiti Putra Malaysia Press, 2000)
Seven duplicate floor pens with 25 day-old commercial chicks were fed a practical type of broiler diet based on maize-palm kernel meal supplemented with varying levels of niacin so that the rations had 15.0, 22.5, 30.0, 37.5, 45.0, 52.5 and 60.0mg of niacin per kg of feed. The treatments were maintained for a period of 42 days. The results based on live weight gain, feed intake, apparent utilisation of nitrogen, metabolizable energy, calcium and phosphorus and carcass characteristics, and the incidence of dermatitis and leg deformities showed that dietary niacin level of 37.5 mg/kg feed was adequate for achieving good nutrient utilisation, optimising productive performance and for maintaining good health.